Modelling the effect of sediment coarseness on local scour at wide bridge piers - Ahmad, Nordila; Mohammed, Thamer Ahmed; Melville, Bruce W.; Ali, Faisal; Yusuf, Badronnisa (Universiti Putra Malaysia Press, 2017)
Experimental data from a physical model of scouring around a cylindrical wide pier embedded in two types of uniform sediment beds are presented. The effects of sediment sizes and various pier widths on scour development and equilibrium scour depth of wide bridge piers are described. Existing literature suggest that the empirical scour prediction equations based on laboratory data over-predict scour depths for large structures. The present study has attempted to fill this gap for a cylindrical wide pier. Further, equations for the estimation of non-dimensional maximum scour depth for a wide cylindrical pier embedded in uniform sediment were proposed as functions of the sediment coarseness.